The Characteristics and Knowledge Level of Mother in The Initial Handling of Toddlers’ Diarrhea Incidence - Puspita Ayu Aryati; Margono Margono; Munica Rita (Jurnal Berkala Epidemiologi, 2018)
Background:. One in five children die from diarrhea every year in Indonesia. Provision of replacement fluids or rehydration fluids as the initial treatment of diarrhea can reduce mortality due to dehydration but the behavior of the community in the initial management of diarrhea in households is not good enough (32.47%). Purpose: This study aimed to identify the level of mothers’ knowledge on the initial treatment of toddler’s diarrhea in Papringan Sleman hamlet in 2015.  Methods: This study was a study that used a cross sectional descriptive study design. The subjects of this study were 54 mothers who had toddlers and lived in Citizen Association (RW) 02 and RW 05 in the Papringan hamlet. Data retrieval is done by interviewing the questionnaire guideline. The measuring instrument of this study uses a closed questionnaire (correct/ incorrect form). The level of knowledge in the initial treatment of toddlers’ diarrhea in this study is based on the correct score obtained by the mothers from the questionnaire sheets. Results: Characteristics of respondents mostly mothers are less then 45 years old, having secondary education, exposure to information, and sources of exposured-information are mostly from direct sources. The level of mother's knowledge is mostly sufficient (57.40%).  Conclusion: Most respondents who are over the age of 45 years, have a secondary education, are exposed to information, and get information from direct sources have sufficient knowledge about early treatment of toddlers’ diarrhea.